(untitled) (ModaPalavra e-periódico, 2014)
This article presents the basic knowledge for the application of a clothing model under the influence of a technique called moulage. This technique is used as an innovating tool, as it facilitates the creativity for a new clothing model while working with the fabric on the body. A qualitative approach was applied which allowed the gathering of descriptive data from the clothing project. It was found that the moulage technique not only amplifies the creativity but it also introduces the anatomy information of the body, its movements and its precise inner lines. Based on the practical experience of a feminine clothing model interpretation, it was demonstrated how the moulage technique can be used, illustrated and described.